2021
DOI: 10.1038/s41598-021-96507-0
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning assisted prediction of the Young’s modulus of compositionally complex alloys

Abstract: We identify compositionally complex alloys (CCAs) that offer exceptional mechanical properties for elevated temperature applications by employing machine learning (ML) in conjunction with rapid synthesis and testing of alloys for validation to accelerate alloy design. The advantages of this approach are scalability, rapidity, and reasonably accurate predictions. ML tools were implemented to predict Young’s modulus of refractory-based CCAs by employing different ML models. Our results, in conjunction with exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…VEC and MT hold the top two positions in predicting the elastic constants. From the previous findings, it is interesting to note the role of the VEC descriptor, which has the top position in descriptor importance in determining the crystal structure [ 20 , 21 , 22 , 23 , 24 , 25 ], Young’s modulus [ 27 , 60 , 61 ], and hardness [ 62 ] of HEAs. The previous study has shown that VEC is the essential feature in determining Young’s modulus of complex concentrated alloys in their ML models [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…VEC and MT hold the top two positions in predicting the elastic constants. From the previous findings, it is interesting to note the role of the VEC descriptor, which has the top position in descriptor importance in determining the crystal structure [ 20 , 21 , 22 , 23 , 24 , 25 ], Young’s modulus [ 27 , 60 , 61 ], and hardness [ 62 ] of HEAs. The previous study has shown that VEC is the essential feature in determining Young’s modulus of complex concentrated alloys in their ML models [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…From the previous findings, it is interesting to note the role of the VEC descriptor, which has the top position in descriptor importance in determining the crystal structure [ 20 , 21 , 22 , 23 , 24 , 25 ], Young’s modulus [ 27 , 60 , 61 ], and hardness [ 62 ] of HEAs. The previous study has shown that VEC is the essential feature in determining Young’s modulus of complex concentrated alloys in their ML models [ 27 ]. Moreover, Roy et al [ 63 ] also found that MT is an essential parameter in predicting Young’s modulus of HEAs using the gradient boosting method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Young's modulus is a measurement of a material's ability to endure tensile or compressive loads. The Valence Electron Concentration (VEC) is defined as the number of valence electrons per formula unit [14]. And the Average Melting Temperature is the average of melting temperatures of all the participating elements.…”
Section: Introductionmentioning
confidence: 99%